2005
DOI: 10.1191/1352458505ms1160xx
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the editor

Abstract: Letter to the editor MSRV, Syncytin and the role of endogenous retroviral proteins in demyelinationSir -A major study on the pathogenesis of multiple sclerosis was published in the October issue of Nature Neuroscience accompanied by a flurry of media reports.The study by Antony and colleagues 1 describes the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The MSRV virion was the first member of the HERV-W family associated with MS and indeed the first member of the HERV-W family described [ 47 ]. The discovery of what initially appeared to be a new class of exogenous retrovirus provoked considerable debate and controversy regarding its origin which still persists at the present time [ 20 , 48 , 49 ]. For example, some authors have proposed that its origin could stem from the expression of isolated genes such as the one now known as ERVW1 , which encodes the cell-cell fusion protein syncytin-1 [ 46 ], while other research teams have suggested the existence of extracellular MSRV particles [ 50 ] or even possibly novel exogenous retrovirus as previously discussed [ 48 , 51 ].…”
Section: Disease Processes and Stimulation Of Herv Expressionmentioning
confidence: 99%
“…The MSRV virion was the first member of the HERV-W family associated with MS and indeed the first member of the HERV-W family described [ 47 ]. The discovery of what initially appeared to be a new class of exogenous retrovirus provoked considerable debate and controversy regarding its origin which still persists at the present time [ 20 , 48 , 49 ]. For example, some authors have proposed that its origin could stem from the expression of isolated genes such as the one now known as ERVW1 , which encodes the cell-cell fusion protein syncytin-1 [ 46 ], while other research teams have suggested the existence of extracellular MSRV particles [ 50 ] or even possibly novel exogenous retrovirus as previously discussed [ 48 , 51 ].…”
Section: Disease Processes and Stimulation Of Herv Expressionmentioning
confidence: 99%
“…Concerning the HERV-W family and its virion-associated MSRV element, an association with multiple sclerosis has been repeatedly and independently demonstrated over the past two decades [12], [18], [20], [21], [22], [23], [24], [25], [26], [27].…”
Section: Introductionmentioning
confidence: 99%